Computational Study of Some Urolithin Derivatives-based Biomass Corrosion Inhibitors on the Fe (110), Cu(111) and Al(111) Surface - Omer, Rebaz A. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2025)
Corrosion poses a significant economic and environmental burden, highlighting the need for sustainable corrosion inhibitors. This study investigates the potential of urolithin derivatives (UroE, UroM5, UroM6, and UroM7) as eco-friendly corrosion inhibitors for Fe(110), Cu(111), and Al(111) surfaces. The research uses Density Functional Theory (DFT) calculations and Monte Carlo (MC) simulations to compute quantum chemical parameters, Fukui function, and noncovalent interactions. The results show that compounds with strong hydrogen bonding interactions form more robust bonds with the metal surface, potentially leading to enhanced corrosion protection. UroM5 demonstrates superior stability and lower reactivity due to its high band gap energy. MC simulations reveal that the adsorption energies of urolithin derivatives on metal surfaces follow a trend: UroM5 > UroM6 > UroE > UroM7, suggesting a stronger binding affinity for these metals. Thermal characteristics, particularly Gibbs free energy, were also investigated. The results suggest that a temperature increase from 825 to 1000 K may induce a transition from physisorption to chemisorption for all chemicals on the metal surface. These comprehensive analyses provide valuable insights into the mechanism and efficiency of urolithin derivatives as corrosion inhibitors, paving the way for the development of novel and eco-friendly anti-corrosion materials.